2015
DOI: 10.32929/2446-8355.2015v24n3p327-344
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição Natural De Espécies Arbóreas Em Áreas Com Diferentes Níveis De Antropização. Atributos Físicos Do Solo

Abstract: Com o surgimento de áreas degradadas, os atributos físicos do solo e os caracteres silviculturais, passaram a ter importância quanto ao entendimento do processo sucessional das espécies arbóreas e no planejamento da recomposição. Objetivou-se avaliar a distribuição natural de espécies arbóreas em áreas com diferentes níveis de antropização, relacionando-os aos atributos físicos do solo. O projeto foi conduzido no município de Selvíria - MS. Foram demarcadas 64 parcelas, onde coletaram-se amostras de solo em qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…No changes were found in the ordering of the other three studied coverages, but the discrimination between the coverages was lower with Inga > Sabia = Acacia (Inga also did not differ from pasture for macro1). Calgaro et al (2015) obtained similar results to those of the present study with the macroporosity of the soil under forest being higher in the 0-0.10 m layer than in the 0.10-0.20 m, while the opposite occurred under grazing possibly as a result of the compaction of the surface layer.…”
Section: /8supporting
confidence: 90%
See 1 more Smart Citation
“…No changes were found in the ordering of the other three studied coverages, but the discrimination between the coverages was lower with Inga > Sabia = Acacia (Inga also did not differ from pasture for macro1). Calgaro et al (2015) obtained similar results to those of the present study with the macroporosity of the soil under forest being higher in the 0-0.10 m layer than in the 0.10-0.20 m, while the opposite occurred under grazing possibly as a result of the compaction of the surface layer.…”
Section: /8supporting
confidence: 90%
“…The macroporosity showed a highly negative correlation with bulk density (R = -0.940 for macro1 and R = -0.898 for macro2, which respectively compose the usual and detailed scales) and a highly positive correlation with total porosity (R = 0.940 and R = 0.898, also respectively for the aforementioned scales). Several studies have shown similar results showing that soil macroporosity is higher in conserved areas (under forest) than under both degraded pasture (Melloni et al, 2008;Calgaro et al, 2015) or intensive farming with either annual or perennial crops (Klein & Libardi, 2002).…”
Section: /8mentioning
confidence: 79%
“…Destaca-se ainda a presença de 11 indivíduos de Curatella americana (lixeira ou simbaíba), abundante no Cerrado central brasileiro, mas ausente em levantamentos no Cerrado s.s. da Chapada do Araripe Araújo, 2007) ou ocorrente com baixa frequência em vegetação savânica sobre tabuleiros prélitorâneos em Fortaleza, Ceará(Moro; Castro, Araújo, 2011). A espécie, pelo seu desempenho e potencial adaptativo, pode ser considerada colonizadora ou, mesmo, nucleadora em áreas savânicas(WINTERHALDER, 1996; REIS, 2010;CALGARO et al, 2015), e pelas adaptações ao fogo, como caule fendilhado e folhas largas, é exemplo típico de um recobrimento fisionômico maior que abrangeu essa área de forma bem mais ampla, ficando hoje apenas essa relíquia vegetacional. ConformeFigueiredo e Fernandes (1987), este fato é evidenciado pela evolução global da paisagem, notadamente no que se refere à estrutura superficial e aos solos.…”
unclassified